Design of continuous bridle multiple-stump anchors. Issue 1 (2nd January 2020) - Lyons, C. Kevin; Sessions, John; Wimer, Jeffrey
ABSTRACT: This paper presents a solution for a three-stump anchor system using a continuous bridle and assuming frictionless blocks. This solution is unique in that the location of the bridle block is not known a priori. A particle swarm optimization was used to estimate the three coordinates of the bridle block and the tension in the bridle. A method employing trilateration was developed to locate the known points in the three-stump anchor system. The advantage to using this method is that only distances between known points need to be measured in the field (angles are not required). For two of the field cases, the ratio of skyline tension to bridle tension was close to the maximum of 6 (bridal tension reduction factor) that could be achieved given the three-stump anchor system, and the other case had a ratio of 4. It was found for shorter bridle lengths, the three-stump anchor system is more sensitive to how in lead the stumps are with the skyline. For three-stump anchor systems, the bridle tension is more strongly controlled by the location of the two outside stumps, and it is relatively insensitive to the location of the middle stump.